Sosialisasi Pengenalan dan Pemanfaatan Penggunaan Layanan Perbankan Syariah Melalui Aplikasi MDIN Pada Nasabah Bank Muamalat Indonesia KCP Mojokerto - Jihan Feby Az Zahra; Asy’ari, Muhammad Alief; Efendhi, Galank Gandha Kusuma (Welfare : Jurnal Pengabdian Masyarakat, 2023)
Mobile banking is a banking service that allows bank customers to make online transactions using only a smartphone. The services offered include financial information (balances, account mutations, interest rates) and financial transactions such as transfers, bill payments, credit purchases, and others. Community service activities have been carried out by IAIN Kediri students regarding the introduction of mobile banking from one of the Islamic banks in Indonesia, namely Bank Muamalat. This socialization is important because, with m-Banking, customers can easily carry out various financial transactions online without having to visit the bank where they are a customer. The approach used is to socialize the benefits of using MuamalatDIN with the community. With this socialization, it is expected to increase the number of customers at Bank Muamalat because using mobile banking will provide convenience to its customers.